2015
DOI: 10.1002/nau.22745
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of activation of pelvic floor muscles in men differs with verbal instructions

Abstract: The pattern of urethral movement measured from transperineal US is influenced by the instructions used to teach activation of the pelvic floor muscles in men. Efficacy of PFM training may depend on the instructions used to train activation. Instructions that optimize activation of muscles with a potential to increase urethral pressure without increasing abdominal EMG/IAP are likely ideal. Neurourol. Urodynam. 35:457-463, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Non‐invasive transperineal ultrasound imaging provides an alternative method to study pelvic floor muscle function and recent investigations using this method have provided new insights . Using this technique muscle activation is quantified by displacement of landmarks in the ultrasound images, and this has been validated against measurement of muscle activation using invasive EMG recordings of SUS, PR, and BC . These studies have confirmed a relation between motion observed on ultrasound and activation of individual pelvic floor muscles in healthy men, thus enabling non‐invasive investigation of the continence mechanism in men with PPI.…”
Section: Introductionmentioning
confidence: 82%
“…Non‐invasive transperineal ultrasound imaging provides an alternative method to study pelvic floor muscle function and recent investigations using this method have provided new insights . Using this technique muscle activation is quantified by displacement of landmarks in the ultrasound images, and this has been validated against measurement of muscle activation using invasive EMG recordings of SUS, PR, and BC . These studies have confirmed a relation between motion observed on ultrasound and activation of individual pelvic floor muscles in healthy men, thus enabling non‐invasive investigation of the continence mechanism in men with PPI.…”
Section: Introductionmentioning
confidence: 82%
“…Men were trained to contract pelvic floor muscles without activation of the abdominal muscles using B‐mode image to provide biofeedback of dorsal displacement of the mid‐urethra. Participants performed a 3‐s maximal voluntary contraction (MVC) of the pelvic floor muscles for two repetitions using the instruction to ‘retract the penis into the body as strongly as possible', which we have shown previously leads to optimal activation of the SUS . The peak MVC EMG amplitude was used to calculate contraction intensity targets set at 5%, 10%, and 15% MVC.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Sapsford et al [7] reported that the PFMs was activated during contraction of the abdominal muscles. Anal contraction is focused on anal muscle contraction [19]. The anal muscle consists of urethral support with PFMs.…”
Section: Discussionmentioning
confidence: 99%